An exploration of designated teachers' work with looked-after children: what constrains and enables attachment-aware practice? - Bhagvanji, Kelley Bernadette (2020)
The research reported in the thesis explored the work of ‘designated teachers’ (hereafter referred to as DTs) who are responsible for supporting the education of looked-after children. Its specific focus is the extent to which the DTs employ attachment-aware practices because it has become increasingly accepted that this approach supports all children to feel safe and maximise their capacity for learning.